The Sentinel of Tomorrow: What Role Will AI Play in Pandemic Prevention? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The shadow of the last global pandemic still looms large, driving a critical re-evaluation of global health security. As the world seeks to fortify its defen...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Precision Medicine